Tulathromycin metaphylaxis increases nasopharyngeal isolation of multidrug resistant Mannheimia haemolytica in stocker heifers - Crosby, William B.; Karisch, Brandi B.; Hiott, Lari M.; Pinnell, Lee J.; Pittman, Alexandra; Frye, Jonathan G.; Jackson, Charlene R.; Loy, John Dustin; Epperson, William B.; Blanton, John; Capik, Sarah F.; Morley, Paul S.; et al. (Frontiers in Veterinary Science, 2023)
Bovine respiratory disease (BRD) is a leading cause of disease in feedlot and stocker calves with Mannheimia haemolytica (MH) as one of the most common etiologies. One of the most effective means of controlling BRD is through metaphylaxis, which involves administering antimicrobials to all animals at high risk of developing BRD. However, increasing prevalence of multidrug resistant (MDR) MH may reduce efficacy of metaphylaxis due to decreased susceptibility to drugs used for metaphylaxis. Primarily, this study aimed to determine the effect of tulathromycin metaphylaxis and subsequent BRD treatment on antimicrobial resistance (AMR) in MH isolated from stocker calves. Secondary objectives included evaluating the effect of metaphylaxis and treatment for BRD on animal health and comparing the genetic relationship of MH isolated. Crossbred beef heifers (n=331, mean weight=232, SD= 17.8 kg) at high risk for BRD were randomly assigned to receive tulathromycin metaphylaxis (META, n=167) or not (NO META, n=164). Nasopharyngeal swabs were collected for MH isolation, antimicrobial susceptibility testing and whole genome sequencing at arrival and 3 (WK3) and 10 (WK10) weeks later. Mixed-effects logistic regression was used to identify risk factors for isolation of MH and MDR MH (resistant to ≥ 3 antimicrobial drug classes) at 3 and 10 weeks, BRD morbidity, and crude mortality. Animals in the META group had higher odds of isolation of MDR MH at 3 weeks (OR (95% CI)=13.08 (5-30.9), P<0.0001) and 10 weeks (OR (95% CI)=5.92 (1.34-26.14), P=0.019) after arrival. There was no difference in risk of isolation of any MH (resistant or susceptible) between META and NO META groups at all timepoints. Animals in the NO META group had 3 times higher odds of being treated for BRD (WK3: OR (95% CI)=3.07 (1.70-5.52), P=0.0002; WK10: OR (95% CI)=2.76 (1.59-4.80), P=0.0002). Antimicrobial resistance genes found within isolates were associated with integrative conjugative element (ICE) genes. Tulathromycin metaphylaxis increased risk of isolation of MDR MH and in this population, the increase in MDR MH appeared to be associated with ICE containing antimicrobial resistance genes for multiple antimicrobial classes. This may have important implications for future efficacy of antimicrobials for control and treatment of BRD.